DESIGN AND IMPLEMENTATION OF AN IMAGE DENOISING AND DEHAZING ALGORITHM FOR ENHANCING DARK CHANNEL PRIOR - Bere, Sachin Sukhdeo; Dhage, Tanuja Shrikant; Hanchate, Dinesh Bhagwan; Baravkar, Bhagyashree Yogesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper delves into the examination of picture dehazing calculations. The fog hinders the visibility of the scene, which in turn disappoints picture processing and computer vision systems. From now on, the nuances in the image won't be apparent. Diminutive air light and air light are the primary determinants of the arrangement of the haze. The whiteness in the picture is caused by air light, and the factor weakening diminishes the picture's differentiation. These problems can be understood if the dehazing calculations are carried out correctly. These computations restore the original image by removing the inception effect.